Government Roles and Limitations in ICT Policy: A Case Study of Korean Telecommunication Rate Policy - WookJoon Sung (International Telecommunications Society (ITS), 2018)
This study is an empirical study on the effect of telecommunication rate policy in Korea. More specifically, it examines the relationship between the Mobile Device Distribution Improvement Act enacted in 2014 and mobile telecommunication rate and device installments. Therefore, the research question is 'How does the Mobile Device Distribution Improvement Act affect consumers' telecommunication rate and device installments?' Six - year data from the KISDI Media Panel was used as the research data, and STATA 13.0 was used for the analysis. As a result of the analysis, since the implementation of Mobile Device Distribution Improvement Act, both the communication charges and the terminal installments of users decreased. Despite these monetary benefits, the policy did not establish transparency in the distribution of the mobile communication market, which was originally intended, and it was limited in that it failed to secure policy compliance or trust from the policy target. It is necessary to enhance policy effectiveness through policy adaptability and trust in communication policy.
Keywords: 330